Relative Performance Analysis of Scheduled Commercial Banks in India : A CAMEL Model Approach - Sahota, Shilpa; Dhiman, Babli (Indian Journal of Finance, 2017)
For sustaining a healthy financial system, it is mandatory to analyze banks frequently for recognition of their strengths and removal of potential vulnerabilities. Banks act as fuel for smooth and efficient functioning of a nation's financial system. The purpose of the present study was to evaluate and compare the financial, operational, and managerial health of selected largest scheduled commercial banks in India with different ownership structure, such as public (State Bank of India), private (ICICI Bank), and foreign banks (Standard Chartered Bank). To achieve this objective, panel data was collected from authentic websites for the period from 2001-2002 to 2010-2011 for banks judged with globally accepted ratio based CAMEL model parameters and average of sub-parameters. In addition to this, one-way ANOVA (parametric test) was applied to statistically measure whether mean variance existed among these banks' ratios and performance. The findings revealed that these banks performed satisfactorily overall after the adoption of reforms. However, SBI was positioned at the top followed by SCB and ICICI Bank in India. Surprisingly, the study observed that there was no difference statistically among these banks in terms of ratios and performance of sub-parameters namely, debt/equity ratio, gross non-performing assets/total assets, income interest/total assets, and liquid assets to total deposits during the research. The study concluded that there was stiff competition among these banks and significantly recommended for proposed banking structure in India. In addition to this, SCB was found to be significantly more efficient during the research period in terms of doing profitable banking business and converting deposits into higher earning advances followed by ICICI Bank and State Bank of India (SBI).